Penerapan Metode Scrum pada Sistem Kehadiran Asisten di Laboratorium Berbasis Android - Rima Tamara Aldisa; Azizah Azizah (Journal of Information System Research (JOSH), 2022)
Attendance is an activity to find out the number of arrivals for laboratory assistants at an agency. Attendance is very necessary for the head of the laboratory to know the level of discipline and diligence of each laboratory assistant. The purpose of this study is to design an android-based laboratory assistant attendance system so that it is easy to check. The method used in this research is the scrum method. The scrum method is used because this method is easy to use, easy to reach. After blackbox testing, it was found that the assistant presence system in this laboratory can run as expected and every menu feature can be used by assistants and the head of the laboratory